A Systematic Review and Meta-Analysis of Anterior Versus Lateral Approach for Laparoscopic Splenectomy. Issue 4 (August 2019) - Rehman, Sheik; Hajibandeh, Shahin; Hajibandeh, Shahab
Abstract : Background: As the experience grew with laparoscopic splenectomy (LS) more surgeons appreciate the advantages of lateral approach compared with conventional anterior approach. In view of this we aimed to compare anterior approach and lateral approach in LS. Methods: We conducted a search of electronic information sources to identify all randomized controlled trials (RCTs) and observational studies comparing anterior and lateral approach in patients undergoing LS. Primary outcomes included need for blood transfusion, intraoperative blood loss, and conversion to open surgery. The secondary outcomes included postoperative morbidity, operative time, time to oral intake, length of hospital stay, need for reoperation, and mortality. Random or fixed-effects modeling were applied to calculate pooled outcome data. Results: We identified 1 RCT and 4 retrospective observational studies, enrolling 728 patients. The baseline characteristics included populations in both groups were comparable. Anterior approach was associated with higher need for blood transfusion [odds ratio (OR), 4.83, 95% confidence interval (CI), 2.31-10.97; P =0.0001]; higher risks of intraoperative blood loss [mean difference (MD), 101.06, 95% CI, 52.05-150.06; P =0.0001], conversion to open surgery (OR, 3.33, 95% CI, −1.32 to 8.43; P =0.01), postoperative morbidity (OR, 3.86, 95% CI, −2.23 to 6.67; P =0.00001) and need for reoperation (OR, 6.91, 95% CI, −1.07 to 44.6; P =0.04); longer operative time (MD, 2.51, 95% CI, −1.43 to 3.59; P =0.00001), time to oral intake (MD, 0.60, 95% CI, −0.14 to −1.07; P =0.01), and length of stay (MD, 2.52, 95% CI, −1.43 to 3.59; P =0.00001) compared with lateral approach. There was no difference in the risk of mortality between the 2 groups (risk difference, 0.00, 95% CI, −0.01 to 0.02; P =0.61). Conclusions: The best available evidence suggests that the lateral approach is superior to anterior approach in LS as indicated by better access, more secure hemostasis, less conversion to open surgery, less morbidity, earlier recovery, and shorter length of hospital stay. The quality of the available evidence is moderate; high-quality RCTs are required to provide more robust basis for definite conclusions.